Wild chimpanzees deprived a leopard of its kill: Implications for the origin of hominin confrontational scavenging. Issue 131 (June 2019) - Nakamura, Michio; Hosaka, Kazuhiko; Itoh, Noriko; Matsumoto, Takuya; Matsusaka, Takahisa; Nakazawa, Nobuko; Nishie, Hitonaru; Sakamaki, Tetsuya; Shimada, Masaki; Takahata, Yukio; Yamagami, Masahiro; Zamma, Koichiro
Abstract: This study reports the first observed case of wild chimpanzees ( Pan troglodytes ) obtaining animal prey freshly killed by a sympatric leopard ( Panthera pardus ) and scavenging it with the leopard still nearby. This observation has important implications for the emergence of confrontational scavenging, which may have played a significant role in human evolution. Many scholars agree that eating meat became important during human evolution, and hominins first obtained meat by scavenging. However, it is debatable whether scavenging behavior was "passive" or "confrontational (power)." The latter is more dangerous, as it requires facing the original predator, and it is thus considered to have been important for the evolution of several human traits, including cooperation and language. Chimpanzees do scavenge meat, although rarely, but no previous evidence of confrontational scavenging has hitherto emerged. Thus, it was assumed that they are averse to confrontation with even leopard-sized predators. However, in the observed case the chimpanzees frequently emitted waa barks, which indicated that they were aware of the leopard's presence but they nevertheless continued to eat the scavenged meat. In addition, we compiled and reviewed 49 cases of chimpanzee encounters with animal carcasses in the Mahale Mountains of Tanzania in 1980–2017. Chimpanzees scavenged meat in 36.7% of these cases, and tended to eat the meat when it was fresh or if the animal species was usually hunted by chimpanzees. However, no evidence indicated that carcasses were avoided when leopard involvement was likely. These results suggest that chimpanzee-sized hominins could potentially confront and deprive leopard-size carnivores of meat.